PENGARUH LATIHAN MEDICINE BALL TERHADAP POWER OTOT LENGAN DAN BAHU NOMOR TOLAK PELURU PADA SISWA PUTRA KELAS X JURUSAN TEKNIK KOMPUTER JARINGAN SMK NURUL FALAH PEKANBARU - Al Amin '; Ramadi '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on observation conducted at the field by researcher in material shot put, researcher found a problem that is the lack of arm and shoulder muscles power so it produces unsatisfactory repulsion where the average of repulsion is below 5 meters. Based on the problem, the researcher gave medicine balltraining with three kinds of exercises: medicine ball chest throw exercises, medicine ball twist throw exercises and medicine ball forward overhead throw exercises that can improve the power of arm muscles and shoulders by providing those training program intensively. The type of this research is experimental research to see the influence of the exercise. The purpose of this research is to see the influence of medicine ball exercise towards arm and shoulders muscles power on shot put number in 20 people of tenth grade male students majoring in computer network engineering at SMK Nurul Falah Pekanbaru. The sampling technique is total sampling, where the sample is the total population. The data collected from pre-test and post-test. Instrument of this research is Two Hand Medicine Ball Put test as a tool to measure arm and shoulder muscles power. Analysis were performed using T test. Based on data analysis and discussion, it can be concluded that there is significant influence of medicine ball exercise towards the power of arm muscles and shoulders on shot put numbers from tenth grade male student majoring in computer network engineering at SMK Nurul Falah Pekanbaru proved by amount of tresult is 10.17 and Ttable is 1,792. Thus tresult> Ttable on the level of ɑ = 0.05.Keywords: Medicine Ball Exercise, Power of Arm Muscles and Shoulders2PENGARUH